Development and Evaluation of Intelligent Tutoring System for Chinese Language Teaching Based on Natural Language Processing - Yue Mengxi (International Journal of Computational and Experimental Science and Engineering, 2025)
The development of computers capable of storing, processing, and responding to inquiries from diverse sources has the potential to transform how individuals learn about the places they visit worldwide. This study investigates the Industrial Training System (ITS), an educational framework designed for the tutoring system for Chinese language teachng effectively. The ITS integrates artificial intelligence (AI) and natural language processing (NLP) technologies to enhance its teaching capabilities. One notable feature of the ITS is its interactive tool that provides assistance to learners when needed. As part of this research project, a prototype computer system was developed to teach the use of Scratch, an art-based application designed to introduce medical student to the fundamentals of coding. By incorporating an open-source tool for natural language understanding (NLU) or processing (NLP) and a Slack-based user interface, the system was capable of answering student queries with accurate responses. The prototype underwent two evaluations to assess its ability to locate objects and facilitate communication with computers to retrieve data. Results indicated that the ontology models employed for this learning tool performed effectively, suggesting that the system holds promise for future implementation as a cloud-based educational solution.